Plant‐mediated resource partitioning by coexisting parasitoids. Issue 6 (15th May 2017) - Xi, Xinqiang; Yang, Yangheshan; Yang, Yonghua; Segoli, Michal; Sun, Shucun
Abstract: Although it has been frequently suggested that resource partitioning of species coexisting at the same trophic level can be mediated by interactions with species at non‐adjacent trophic levels, empirical evidence supporting this claim is scarce. Here we demonstrate that plants may mediate resource partitioning for two parasitoids that share the same herbivorous host. The tephritid fly Tephritis femoralis is the primary pre‐dispersal seed predator of two Asteraceae species, Saussurea nigrescens and Anaphalis flavescens, both of which dominate the plant community in the alpine meadows of the Tibetan Plateau. Field surveys and molecular barcoding analyses showed that the identity of the fly's main predator depended on the plant in which the fly developed. Tephritid flies that developed in S. nigrescens were preyed upon mainly by the parasitoid wasp Pteromalus albipennis, while the parasitoid Mesopolobus sp. was the main predator of flies that developed in A .  flavescens . Microcosm experiments revealed that P. albipennis could not exploit the host flies within the capitula of A .  flavescens due to food limitation (capitula are too small), while Mesopolobus sp. could not exploit the host flies within the capitula of S. nigrescens due to its inability to reach the host with its ovipositor (capitula are too large). Such bottom‐up control of plant species traits may facilitate the coexistence of parasitoid wasps sharing a common host in this system. We suggest that interactions between non‐adjacent trophic levels may potentially promote species coexistence and diversity in biological communities.